2010
DOI: 10.1002/cbic.200900778
|View full text |Cite
|
Sign up to set email alerts
|

2‐(1‐Ethynylpyrene)‐Adenosine as a Folding Probe for RNA—Pyrene in or out

Abstract: A series of short RNA duplexes containing one or two 1-ethynylpyrene-modified adenine bases was synthesised. The melting behaviour of these duplexes was examined by monitoring temperature-dependent pyrene fluorescence. In the singly modified RNA duplexes, the bases flanking the ethynylpyrene-rA were varied to examine the sequence specificity of the fluorescence change of pyrene upon RNA hybridisation. Because an increase in pyrene fluorescence upon melting of the duplex can be correlated with intercalation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 58 publications
(80 reference statements)
2
23
0
Order By: Relevance
“…Substitution of pyrene at a single position is possible—for symmetry reasons, only the positions 1, 2 and 4 are distinct—and has frequently been utilized to generate various fluorescent nucleoside analogues for nucleic acids research . In general, both, the position of the substitution and their nature were found to affect the electronic and spectral properties of pyrene derivatives .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of pyrene at a single position is possible—for symmetry reasons, only the positions 1, 2 and 4 are distinct—and has frequently been utilized to generate various fluorescent nucleoside analogues for nucleic acids research . In general, both, the position of the substitution and their nature were found to affect the electronic and spectral properties of pyrene derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Substitution of pyrene at as ingle position is possible-for symmetry reasons, only the positions 1, 2a nd 4a re distinctand has frequently been utilized to generate various fluorescent nucleoside analogues for nucleic acids research. [9][10][11][12][13][14][15] In general, both, the position of the substitution and their nature were found to affect the electronic and spectral properties of pyrene derivatives. [16][17][18][19][20] Linked to nucleosides,p yrene often forms pronouncedc harget ransfer( CT) states after excitation, acting as electron donor and acceptor when linked to pyrimidines andg uanosine, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrene fluorophore appended on adenine A PY , A P and G P has allowed these nucleobases to be excited at long ultraviolet to short blue ranges (380 to 420 nm) while emitting blue light (450 to 480 nm) (Fig. 3d) 3234 . In some rarer cases, the 7 position can also be appended with fluorescence extensions, with replacement of the nitrogen at the 7 position with carbon to preserve aromaticity.…”
Section: Purine Architecture Modificationsmentioning
confidence: 99%
“…Another favorable characteristic is the ability to form excimers upon close proximity of two PyAs of complementary strands in the minor groove [4]. Experiments revealed that PyA is also able to intercalate into RNA depending on the flanking bases in 5' direction of the modified base [5,6]. A G-C base pair leads to the intercalation of PyA, whereas A-U base pairs do not show this behavior.…”
Section: Introductionmentioning
confidence: 99%